THE USE OF GOOGLE TRANSLATE IN TRANSLATING FROM ENGLISH INTO BAHASA INDONESIA - Hilmi Fahmiyati Gustiani; Muhamad Taufik Hidayat (EEAL Journal (English Education and Applied Linguistics Journal), 2019)
This study is aimed to investigate whether quantum learning method is effective to develop students’ reading comprehension. The quantitative research method was used with the time series-quasi experimental study as the research design and it was conducted in one of junior high schoolsin Garut with 30 students of eighth-graders as the sample. The data in this study were collected by using pretest and series of post-tests. The result has shown that quantum learning method is effective in developing students’ reading comprehension. Therefore, quantum learning method can be an alternative to be applied in teaching reading comprehension.